2014
DOI: 10.1044/cicsd_41_s_12
|View full text |Cite
|
Sign up to set email alerts
|

A Computer-Based Readability Analysis of Consumer Materials on the American Speech-Language-Hearing Association Website

Abstract: reading grade levels displayed. Results: According to 4 different readability formulas, an overwhelming majority (85.4% or more) of the 225 consumer documents exceeded the 5th-to 6thgrade reading levels recommended by health literacy experts. Conclusion: Many consumer articles on the ASHA website are likely to be of limited value to individuals with low health literacy. As a result, consumers might misinterpret or misapply information contained in the articles, putting themselves or those they care for at risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 42 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…This step is essential if consumer‐oriented literature on the Internet is to be of value, particularly to those with low or limited health literacy (Atcherson et al. (). Numerous methods exist to assess readability of website content.…”
Section: Methods For Systematic Review and Website Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This step is essential if consumer‐oriented literature on the Internet is to be of value, particularly to those with low or limited health literacy (Atcherson et al. (). Numerous methods exist to assess readability of website content.…”
Section: Methods For Systematic Review and Website Analysismentioning
confidence: 99%
“…Analysis of the readability of websites is related to the concept of health literacy, which refers to the consumer's ability to read and understand health-related material and subsequently make an informed choice (Storms, Claes, Aertgeerts, & van den Broucke, 2017). This step is essential if consumer-oriented literature on the Internet is to be of value, particularly to those with low or limited health literacy (Atcherson et al (2014). Numerous methods exist to assess readability of website content.…”
Section: Compute Readabilitymentioning
confidence: 99%
“…Consequently, it is the readability of a document that makes it comparably easier, or more difficult, to read than another (DuBay, 2004). If the reading level of a document exceeds that which the intended audience is capable of comprehending, they are at risk of not only failing to understanding the material, but also of giving up entirely (Atcherson et al, 2014;DuBay, 2004). As such, the concept of readability poses a difficult question for healthcare providers.…”
Section: Readabilitymentioning
confidence: 99%
“…Previous research has consistently found that the readability of health information (including patient-reported outcome measures used within the healthcare field) has exceeded those levels recommended by health literacy experts (D'Alessandro et al, 2001;Edmunds et al, 2013;Hansberry et al, 2014;Kong & Hu, 2015;Paasche-Orlow et al, 2003;Rudd et al, 2000;Sabharwal et al, 2008;Safeer and Keenan, 2005;Sharma et al, 2014;Svarstad et al, 2003;Zorn et al, 2004). The field of audiology is no exception (Atcherson et al, 2013(Atcherson et al, , 2014Donald & Kelly-Campbell, 2016;Joubert & Githinji, 2014;Laplante-Lévesque, Brännström, et al, 2012;Ritchie et al, 2016;Swartz, 2010). More specifically, recent research into the readability of audiologic PROMs continues to reveal that the reading grade levels of these questionnaires consistently exceed the recommended 4 th to 6 th grade (Atcherson et al, 2011(Atcherson et al, , 2013Kelly-Campbell et al, 2012).…”
Section: Aim and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation